Compliance with the principle of autonomy of pregnant women during their childbirth / Cumplimiento del principio de autonomía de las mujeres gestantes durante su parto - Hernández Benítez, María Dolores (Medicina e Morale, 2019)
Objective: to determine the degree of compliance with the requests that women reflect in their birth plans and determine their influence on the main obstetric and neonatal outcomes. Method: retrospective, descriptive and analytical study with 178 women with a delivery plan in third level hospitals. Inclusion criteria: low risk pregnancy, cephalic presentation, single-term delivery. We excluded scheduled and urgent caesarean sections without labor. A descriptive and inferential analysis of the variables was carried out. Results: the delivery plan was fulfilled mostly in only 37% of the women. The group of women where compliance was low (less than or equal to 50%) had a percentage of caesarean sections of 18.8% and their children had worse results in Apgar test and cord pH; while in women with high compliance (75% or greater), the percentage of caesarean sections fell to 6.1% and their children obtained better results. Conclusion: the delivery plan has a low degree of compliance. The greater the compliance, the better the maternal and neonatal results. It can be an effective tool in achieving better results in the mother and her child. Measures are needed to improve the degree of compliance. ---------- Objetivo: conocer el grado de cumplimiento de las solicitudes que las mujeres reflejan en sus planes de parto y determinar su influencia en los principales resultados obstètricos y neonatales. Mètodo: estudio retrospectivo, descriptivo y analítico con 178 mujeres con plan de parto en hospitales de tercer nivel. Criterios de inclusión: gestación bajo riesgo, presentación cefálica, parto Ãºnico a tèrmino. Se excluyeron cesáreas programadas y urgentes sin trabajo de parto. Se realizó un análisis descriptivo e inferencial de las variables. Resultados: el plan de parto se cumplió mayoritariamente solo en el 37% de las mujeres. El grupo de mujeres donde el cumplimiento fue bajo (menor o igual al 50%) tuvo un porcentaje de cesáreas del 18,8% y sus hijos tuvieron peores resultados en test de Apgar y pH de cordón; mientras que en mujeres con cumplimiento alto (75% o mayor), el porcentaje de cesáreas cayó al 6,1% y sus hijos obtuvieron mejores resultados. Conclusión: el plan de parto tiene un grado de cumplimiento bajo. A mayor cumplimiento mejores son los resultados maternos y neonatales. Puede constituir una herramienta eficaz en la consecución de mejores resultados en la madre y su hijo. Son necesarias medidas que mejoren su grado de cumplimiento.